(untitled) (Journal of Global Arts Studies, 2025)
Background: Traditional choreography uses the stage as a medium, and its core lies in the construction of narrative and emotional expression through the continuous movement of the dancer’s body in three-dimensional space. However, in screendance, the logic of choreography has undergone a fundamental shift. Objective: The purpose of this study is to reveal the cognitive conflicts and solutions between dance and film in the creative process of screendance through a practice-based approach, taking the creation of Nanyin into the Painting as a case. Methods: The research methodology is composed of two parts: literature research method and auto-ethnographic fieldwork research. Through the study of the interactive relationship between live choreography and camera scheduling during the creative process, a research chain of “problem-strategy-verification” was formed and Time-Space-Corporeal Cognitive Transformation Framework (Cultural Anchor) was further validated. Results: This research found that the cognitive conflicts between dance and film can be resolved through the Time-Space-Corporeal Cognitive Transformation Framework (Cultural Anchor): in terms of time, the rhythm and poetic image of Nanyin are used to reconcile the real-time nature of dance and the fragmentation of videos; in terms of space, architectural features and filming techniques are employed to reconcile dimensional conflicts; in terms of movement, cultural symbols are utilized to balance the continuity of the body and the selectivity of the camera. Conclusion: Time-Space-Corporeal Cognitive Transformation Framework (Cultural Anchor) demonstrates its innovative applications in culture related screendance, providing new methods for screendance makers, and revealing the cognitive transformation mechanism of the interactions among the body, technology, and culture.